(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The significance of dietary nutrition in the prevention of cardiovascular diseases (CVD) has been well established [3,4]. Proper nutritional regimen and healthy lifestyle habits are among the key strategies for preventing complications associated with these conditions. Educating the population about principles of healthy living—including rational nutrition, physical activity, and smoking cessation—is crucial.